Model for Ray-Based UTD Simulations of the Human Body Shadowing Effect in 5G Wireless Systems - Łukasz Januszkiewicz (International Journal of Antennas and Propagation)
Shadowing effects caused by the obstructing presence of a human body can result in increased path loss in indoor wireless systems. This paper proposes a simplified model of a human body for use in ray-tracing simulations of indoor wireless communication systems based on the uniform theory of diffraction (UTD). The human body shadowing effect was first investigated using measurements and computer simulations employing the finite-difference time-domain method (FDTD). Based on the results, a human body model was elaborated for use in ray-based Remcom XGtd software. The model was developed for the 3.6 GHz band, which has been allocated for 5G wireless systems in many countries.